The Price of Winning and the Impact on the NCAA Community - Emily S. Sparvero; Stacy Warner (University of Kansas Libraries, 2013)
In many cases, athletics department spending has been spurred by a desire to field more competitive athletics programs, and it has been assumed that spending more would result in greater on-the-field success for the athletics program. However, little empirical evidence exists to support this assumption, and few studies have explored financials trends related to cost-benefit of intercollegiate athletics program. Thus, the aim of this study was to determine the relationship between on-the-field success and spending while also exploring current trends. The authors drew longitudinal data from EADA reports and then examined the association with Directors' Cup rankings at the end of these respective seasons. The results indicated that a relationship between overall expenses and on-the-field success does exist, and points to operating expenses, rather than coaching salaries and recruiting expenses, as having greatest influence on this relationship. The cost-benefit analysis and trends over time are also explored and discussed.